Nonablative Fractional Resurfacing - Kaufman, Joely; Liao, Sophie (Facial Plastic Surgery, 2014)
Since its introduction in 2004 by Manstein et al, fractional resurfacing has revolutionized the manner in which we treat photoaging. Fractional resurfacing delivers microscopic beams of light to the skin resulting in coagulation or vaporization of fragments of the epidermis and dermis. The wavelengths of these devices may vary, yielding different clinical results. This article will discuss the various uses of fractional ablative and nonablative devices available today.
Keywords: laser; fractional; nonablative; photoaging